Effect of nanoclay on the properties of medium density fiberboard (MDF) - Sayed mohammad javad Mosavi hosseini; Mohammad mehdi Faezipoor; Hossein Usefi (تحقیقات علوم چوب و کاغذ ایران, 2011)
The effect of using nanoclay on MDF properties was investigated. Sodium montmorolonit (NA+MMT) was used in three levels of 0, 3 and 6 percent based on dry weight of two resins of urea formaldehyde (UF) and Methylene diphenyl diisocyanate (MDI). Modulus of rupture (MOR), modulus of elasticity (MOE), internal bonding (IB), thickness swelling (TS) and water absorption (WA) of MDF were measured based on EN standard. Results demonstrated that with the increase of nanoclay in both UF and MDI resins MOR and MOE of MDF increased significantly in such a way that with the use of UF containing 6% nanoclay MOR increased by 33%. Although, IB was significantly affected by UF containing nanoclay, MDI containig nanoclay caused reduction in IB. WA and TS of MDF made from MDI did not show significant variation by increase of nanoclay but those made from UF resin positively affected by adding nanoclay in such a way that MDF made from 3% nanoclay showed 41% loss in TS compared to those made from pure UF.